1996
DOI: 10.1212/wnl.46.1.231
|View full text |Cite
|
Sign up to set email alerts
|

[sup 123 I] beta-CIT/SPECT imaging demonstrates bilateral loss of dopamine transporters in hemi-Parkinson's disease

Abstract: We have used in vivo single-photon emission computed tomography (SPECT) of the dopamine transporter with 2 beta-carboxymethoxy-3 beta-(4-iodophenyl)tropane ([123I] beta-CIT) to investigate striatal dopamine transporter loss in patients with early Parkinson's disease (PD). Striatal uptake of ([123I] beta-CIT was compared in eight early-PD patients with exclusively hemi-parkinsonism and eight age- and sex-matched healthy subjects. [123I] beta-CIT striatal uptake was reduced by approximately 53% contralateral and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
178
1
10

Year Published

1997
1997
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 344 publications
(204 citation statements)
references
References 8 publications
15
178
1
10
Order By: Relevance
“…This implies that both methods can possibly also be used to identify patients in a preclinical phase of the disease. This has been confirmed by others [16,18,21].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This implies that both methods can possibly also be used to identify patients in a preclinical phase of the disease. This has been confirmed by others [16,18,21].…”
Section: Discussionsupporting
confidence: 89%
“…SPECT imaging with FP-CIT produces a high target to background ratio. Several studies have demonstrated that striatal FP-CIT uptake is reduced in patients with PD compared to healthy controls [14][15][16][17][18][19][20][21][22]. It has been shown that striatal uptake values of FP-CIT SPECT and F-DOPA PET correlate well with each other in patients with different stages of PD [15,23].…”
Section: Introductionmentioning
confidence: 99%
“…This aging effect was also more pronounced in the patients aged 32-45 years than in those older than 45 years. As mentioned earlier, Marek et al [7], using [ 123 I]β-CIT, found a significant decline in striatal binding with age in PD patients (n=8), while Tedroff et al [6] failed to find such a decline using 11 C-nomifensine (n=6). However, in these studies, involving a relatively small number of patients, neither the severity of PD nor the medication was taken into account, which makes it difficult to estimate reliably the contribution of age.…”
Section: Discussionmentioning
confidence: 87%
“…Using 11 C-nomifensine PET, Tedroff et al [6] did not find any significant decline in binding with age (n=6), whereas Marek et al [7], using [ 123 I]β-CIT SPET, did (n=8).…”
Section: Introductionmentioning
confidence: 91%
“…It is, therefore, important to diagnose the disease in its early stages with the help of all available diagnostic methods to rule out symptomatic parkinsonisms or parkinsonian syndromes, other than idiopathic PD, and start specific treatment. In patients with recent onset PD or hemiparkinsonism, a 50% decrease in presynaptic transporters has been observed in the putamen contralateral to the symptomatic side, and a 30% decrease in the putamen ipsilateral to symptoms (Marek et al, 1996;Tissingh et al, 1998). Evaluation of pre-synaptic dopaminergic integrity using 123-I Ioflupane in PD is a useful tool to: diagnose early stages, characterize disease severity and progression (Seibyl et al, 1995;Rinne et al, 1995), predict PD bilateralization in patients in a very early stage (when symptoms often involve only one side of the body) (Marek et al, 2001), assess the efficacy of agents slowing the course of disease and, more controversially, differentiate an idiopathic disorder from other forms of parkinsonian syndromes (Innis et al, 1993).…”
Section: Degenerative Parkinsonismsmentioning
confidence: 99%